2016
DOI: 10.5658/wood.2016.44.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement of Oil Palm Trunk Properties by Close System Compression Method

Abstract: Densification of the inner part of oil palm trunk (OPT) by the close system compression (CSC) method was performed in this study. The effects of the compression temperature and time on the anatomical, physical and mechanical properties of OPT were evaluated. The inner part of OPT with an initial average density of 0.3 g/cm 3 was used as samples. Oven-dried samples were immersed in water and vacuumed until fully saturated and then compressed by CSC at 120, 140, 160 or 180℃ for 10, 20, 30 or 40 min. The anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…Salah satu usaha yang dilakukan untuk meningkatkan sifat fisis dan mekanis batang kelapa sawit adalah dengan cara memadatkannya (densifying by compression). Perlakuan pemadatan secara signifikan dapat meningkatkan sifat fisis dan mekansi seperti yang disampaikan oleh Kutnar and Kamke [8] dan Hartono et al [5]. Kutnar and Kamke [8] mengemukakan bahwa pemadatan dengan tekanan 5,5 MPa pada kayu poplar hibrida (Populus deltoides × Populus trichocarpa) mampu meningkatkan kerapatan 98%-208%.…”
Section: Pendahuluanunclassified
“…Salah satu usaha yang dilakukan untuk meningkatkan sifat fisis dan mekanis batang kelapa sawit adalah dengan cara memadatkannya (densifying by compression). Perlakuan pemadatan secara signifikan dapat meningkatkan sifat fisis dan mekansi seperti yang disampaikan oleh Kutnar and Kamke [8] dan Hartono et al [5]. Kutnar and Kamke [8] mengemukakan bahwa pemadatan dengan tekanan 5,5 MPa pada kayu poplar hibrida (Populus deltoides × Populus trichocarpa) mampu meningkatkan kerapatan 98%-208%.…”
Section: Pendahuluanunclassified
“…The results showed that compression by the CSC method successfully increased the density, modulus of elasticity (MOE), modulus of rupture (MOR), and compressive strength of S-OPT up to 90%, 190%, 155%, and 120%, respectively (Hartono et al, 2016). The impregnation of phenol formaldehyde (PF) resin into OPT and wood has been reported to improve dimensional stability (Furuno et al, 2004;Rowell, 2005), physical and mechanical properties (Shams et al, 2006;Bakar et al, 2013), and increased the resistance against fungal decay and termites attack (Nabil et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…CSC is a compression method to improve permanent fixation of compressive deformation in a short time by hygrothermal treatment using moisture in wood or other lignocellulosic materials (Inoue et al, 1993). Detail description of the CSC method can be seen in our previous publication (Hartono et al, 2016).…”
Section: Pf Resin Impregnation and Densification By Csc Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous study, Hartono et al [10] reported that densification of the S-OPT by CSC successfully increased the density, modulus of elasticity, modulus of rupture, and compressive strength of S-OPT up to 90%, 190%, 155%, and 120%, respectively. Therefore, the objective of this study was to evaluated the fixation of S-OPT (based on recovery of set and weight loss) by close system compression (CSC).…”
Section: Introductionmentioning
confidence: 99%